Value of Students’ Study Motivation on Geography Lesson In SMA Gowa Raya Sungguminasa Kabupaten Gowa - Azhim, Muhamad Ihsan; Abbas, Ibrahim; Leo, Muhammad Nur Zakariah (Universitas Negeri Makassar, 2017)
The objective of the research was to find out the students’ study motivation in learning geography. The research method applied on this research was descriptive. Descriptive method aimed at finding the level of students’ study motivation in learning geography at the first grade students of SMA Gowa Raya Sungguminasa. The instrument used to know thelevel of student’s study motivation in this research is questionnaires consist of 32 items for students’ motivation .The questionnaires are giving to the 19 sample of this research. After calculating the questionnaires of students’ study motivation, it is known that the level of students’ study motivation is at good category. Meanwhile the other things that influence the students’ study motivation are passion and wish of student to be succesful, the push and need to study, there is hope and desire, appreciation in learning, there is interesting activity in learning and study in conducive environment of study.